Mycobacterium abscessus pulmonary infection and associated respiratory function in cystic fibrosis-like βENaC mice - Pearce, Camron M.; Shaw, Timothy D.; Podell, Brendan; Jackson, Mary; Henao-Tamayo, Marcela; Obregon-Henao, Andres; Lam, Ha; Alshiraihi, Ilham M.; O'Neal, Wanda; Livraghi-Butrico, Alessandra; Hickey, Anthony J.; Meibohm, Bernd; et al. (Frontiers in Tuberculosis, 2024)
BackgroundIntroduction: Chronic pulmonary infection with Mycobacterium abscessus (M. abscessus) is a significant cause of morbidity and mortality in people with cystic fibrosis (CF). Developing an animal model of M. abscessus pulmonary infection, especially under CF conditions, is essential to understanding clinical pulmonary M. abscessus infection. βENaC transgenic mice are known to develop spontaneous CF-like disease characterized by airway mucus obstruction and inflammation. The aim of this study was to evaluate the suitability of βENaC mice as a preclinical model and characterize their respiratory function during M. abscessus lung infection.Mice received an intrapulmonary aerosol of M. abscessus using a high-pressure syringe device (Penn-Century) for subsequent characterization of disease progression and respiratory function. Whole body unrestrained plethysmography (WBP) data was collected to monitor lung function and endpoints determined organ bacterial burden and associated pathology.Results: Endpoint CFU data in the lung and spleen showed that there was no significant difference in bacterial clearance between βENaC and WT mice. WBP data showed an impairment in overall respiratory function during and after M. abscessus infection in both strains of mice. Interestingly, even in wildtype control mice, lung dysfunction persisted after bacterial clearance.Even with CF-like features, the βENaC transgenic mice cleared M. abscessus at a similar rate than WT mice, however, the associated respiratory monitoring revealed that there are long-term implications of M. abscessus lung exposure. The clear decline in respiratory function, even after M. abscessus clearance, suggests that WBP coupled animal modeling provides important insight that is relevant to disease burden and treatment efficacy. The M. abscessus clearance in the βENaC mice may help improve the fields understanding of CF-modulated immune deficiencies in M. abscessus pulmonary infection.